Porous titanium scaffolds produced by powder metallurgy for biomedical applications - Vasconcellos, Luana Marotta Reis de [UNESP]; Oliveira, Marize Varella de; Alencastro Graça, Mário Lima de; Vasconcellos, Luis Gustavo Oliveira de [UNESP]; Carvalho, Yasmin Rodarte [UNESP]; Cairo, Carlos Alberto Alves (FapUNIFESP (SciELO), 2008)
Porous titanium scaffolds are promising materials for biomedical applications such as prosthetic anchors, fillers and bone reconstruction. This study evaluated the bone/titanium interface of scaffolds with interconnected pores prepared by powder metallurgy, using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Porous scaffolds and dense samples were implanted in the tibia of rabbits, which were subsequently killed 1, 4, and 8 weeks after surgery. Initial bone neoformation was observed one week after implantation. Bone ingrowth in pores and the Ca/P ratio at the interface were remarkably enhanced at 4 and 8 weeks. The results showed that the interconnected pores of the titanium scaffolds promoted bone ingrowth, which increased over time. The powder metallurgy technique thus proved effective in producing porous scaffolds and dense titanium for biomedical applications, allowing for adequate control of pore size and porosity and promoting bone ingrowth.
Keywords: Biomedical; Osseointegration; Porosity; Titanium; Aluminum powder metallurgy; Applications; Bone; Interconnection networks; Metallurgy; Ores; Powder metallurgy; Powders; Biomedical applications; Bone ingrowths; Bone reconstructions; Ca/P ratios; Interconnected pores; Porous scaffolds; Porous titaniums; Promising materials; Titanium scaffolds; Scaffolds